THE EFFECT OF CHORAL READING STRATEGY ON STUDENTS’ READING FLUENCY ABILITY AT THE FIRST YEAR IN SMK TARUNA SATRIA PEKANBARU - Sari, Maya Puspita; Eliwarti, Eliwarti; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was aimed to know the effect of Choral Reading Strategy on students? reading fluency ability in SMK Taruna Satria Pekanbaru. This research was pre-experimental research with one group pretest-posttest design model. The first year students in academic were 2018/2019 chosen as the population of this research. The sample of this research was class 1 TKJ 1 that consisted of 29 students chosen by cluster sampling technique. Descriptive text was chosen as the instrument of this research. To collect the data the students read the text aloud individually. The reading text consisted of 158 words. Ms. Excell 2013 was used to analyze the data. Based on the results, the mean score of post-test was higher than the mean score of pre-test. The mean score for pre-test was 62.10 while the mean score in post-test was 65.47. The value of t-test was higher than t-table (6.1026 > 2.77) at 1% of the significant level. In short, the null hypothesis (H0) of this research was rejected. It can be concluded that, there is significant effect of choral reading strategy on students? reading fluency.Keywords: Choral Reading Strategy, Reading Fluency, Descriptive Text